L = 3w - 7
Lw = 66
Lw = 66
(3w - 7)w = 66
3ww - 7w - 66 = 0
the above quadratic equation is in standard form, with a=3, b=-7, and c=-66
to solve the quadratic equation, by using the quadratic formula, copy and paste this:
3 -7 -66
into this solver: https://sooeet.com/math/quadratic-equation-solver.php
the quadratic has two real roots at:
w = 6
w = -3.6666666
The negative root doesn't fit the problems statement, so use the positive root instead:
w = 6
L = 3w - 7
L = 3*6 - 7
L = 11
Answer:
w = 6 yds
L = 11 yds